Extracorporeal Membrane Oxygenation Cannula–Related Infections: Epidemiology and Risk Factors. Issue 4 (1st June 2021) - Winiszewski, Hadrien; Boyadjian, Charles; Besch, Guillaume; Soumagne, Thibaud; Jeanney, Martin; Pili-Floury, Sebastien; Fournier, Damien; Belon, François; Chocron, Sidney; Capellier, Gilles; Perrotti, Andrea; Piton, Gaël
Abstract : Although being a potential major source of infection in extracorporeal membrane oxygenation (ECMO) patients, data regarding cannula-related infections (CRI) remain scarce. We therefore aimed at describing the epidemiology of CRI among critically ill patients supported by ECMO. Between October 2017 and November 2019, adult patients supported by either venoarterial (VA), venopulmonary arterial, or venovenous (VV) ECMO for more than 24 hours were prospectively enrolled. When CRI was suspected, cannula swab and subcutaneous needle aspirate samples were obtained for microbiological culture. Cannula tips were systematically sent for culture at the time of ECMO removal. Primary end-point was CRI, which was defined by sepsis or local sign of cannula infection and at least one positive culture among swab, subcutaneous needle aspirate or tip. Multivariate analysis was performed to identify risk factors of CRI. Hundred patients were included, including 77 VA, 12 venopulmonary arterial, and 11 VV ECMO. Cannula-related infections were diagnosed after a median duration of ECMO of 10 [7–13] days. Rate of CRI was 24%, including 10% with bacteremia. Most frequent involved pathogens were Enterobacteriaceae (n = 14), Enterococci (n = 8), and coagulase-negative Staphylococci (n = 7). By multivariate analysis, diabetes and ECMO duration were independently associated with CRI.